2003
DOI: 10.1177/0310057x0303100106
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Peripheral and Central Venous Pressures in Critically Ill Patients

Abstract: We conducted a prospective study to determine the relationship between central (CVP) and peripheral (PVP) venous pressures in critically ill patients. CVP and PVP were measured on five different occasions in 20 critically ill patients in the intensive care unit. Results showed that the mean difference between PVP and CVP was 4.4 mmHg (95% CI= 3.7 to 5.0). However, PVP might be 1.9 mmHg below (95% CI=0.7 to 3.1) or 10.6 mmHg above (95% CI=9.4 to 11.8) the CVP. The mean difference between changes in PVP and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…2 They observed a bias of 4.4 mm Hg (95% CI 3.7-5.0). They noticed extreme variation in PVP measurements, as high as 10.6 mm Hg above simultaneous CVP measurement.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…2 They observed a bias of 4.4 mm Hg (95% CI 3.7-5.0). They noticed extreme variation in PVP measurements, as high as 10.6 mm Hg above simultaneous CVP measurement.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown evidence that CVP can be estimated by peripheral venous pressure (PVP) measurements, introducing PVP as a hemodynamic monitoring parameter in different clinical settings such as the operating room and intensive care units. 1,2 It is well known that under general anesthesia, an inevitable initial rapid decrease in body temperature occurs, followed by a linear decrease for 3-4 hours. 3,4 The classic physiologic response to hypothermia is peripheral vasoconstriction.…”
mentioning
confidence: 99%
“…With improvement of central venous catheterization techniques in the mid-20th century, Pedersen [5] observed that CVP and PVP are related. However, the use of PVP over CVP has been evaluated only in recent years [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by Charalambous et al [6], PVP and CVP were compared in 20 critically ill patients. They observed a bias of 4.4 (95% CI, 3.7-5.0).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly thirty years later another trial correlated external jugular venous pressures with CVP in anesthetized surgical patients [6]. Several recent studies have demonstrated a strong correlation between PVP and CVP in different patient populations [7][8][9][10][11][12][13]. Patients with liver failure undergoing surgical procedures have not been evaluated for PVP/CVP correlation.…”
Section: Introductionmentioning
confidence: 99%